The Phenomenon of Cancel Culture and Doxing on Social Media X (Twitter): A Criminological Study of Digital Violence - Allifa Mutia Akbar; Emilia Amarda; Muh Arfandi; St. Alifyani Zahra; ST. Nur Hajariani (Civiliza Publishing, 2026)
One of the types of digital violence that is increasing in the information technology era is the phenomenon of cancel culture and doxing on social media such as X (Twitter). This practice not only affects the victim's reputation but also causes psychological stress, social harm, and a threat to one's privacy and security. The high use of social media in Indonesia is not balanced with sufficient legal protection against the spread of personal data and digital intimidation, so it is important to investigate this topic. How the culture of cancel and doxing in X is considered as a form of digital violence is the purpose of this study. In addition, this study looks at how effective the law, especially the Electronic Information and Transaction Act (UU ITE) and the Personal Data Protection Act (UU PDP), in punishing people who commit street violations. This research uses a qualitative approach for normative jurispris. Laws and regulations, legal doctrines, and relevant literature are studied. Legal theory, literature, and laws and regulations are studied. The research results show that cancel culture and doxing have a pattern to put pressure on victims through the formation of public opinion, collective social punishment, and the dissemination of personal data. In addition, although the ITE Law and the PDP Law provide a basis for protecting privacy and personal data, doxing has not been regulated as a criminal offense. Therefore, this research is the basis for the development of better legal policies and digital protection to create a social media space that is safe, fair, and respects people's privacy rights.